THE EFFECT OF COGNITIVE BEHAVIORAL THERAPY (CBT) ON POST-DISASTER ANXIETY - Rahayu, Rita; Bin Sansuwito, Tukimin; Wati, Nenden Lesmana (Rifapublisher.id, 2025)
Background: Anxiety is a common psychological impact experienced by disaster survivors, including flood survivors. They often develop excessive fear of rain, thunder sounds, and the potential for recurring floods, which may lead to post-traumatic stress disorder (PTSD). One of the evidence-based psychological therapies effective in addressing anxiety is Cognitive Behavioral Therapy (CBT), which works by altering negative thought patterns and maladaptive behaviors. Objective: This study aims to analyze the effect of CBT on anxiety levels among flood disaster survivors in two disaster-prone areas. Methods: This study employed a quasi-experimental design with a pre-test and post-test control group design. The sample consisted of 60 flood survivors divided into two groups: the intervention group (n=30) and the control group (n=30). Anxiety levels were measured using the Beck Anxiety Inventory (BAI) before and after the intervention. Data were analyzed using a paired t-test to assess the effectiveness of CBT in reducing anxiety. Results: The analysis showed a significant difference in anxiety levels before and after the intervention in the experimental group (t(14) = 5.21, p < 0.001), while no significant change was found in the control group (t(14) = 1.32, p = 0.201). The average anxiety score in the intervention group decreased from 36.7 to 15.6, indicating that CBT was effective in reducing anxiety among flood disaster survivors. Conclusion: CBT has been proven effective in reducing anxiety levels among flood survivors by helping them change negative thought patterns and improve coping mechanisms. Implementing CBT can serve as a psychological intervention strategy in post-disaster recovery programs to enhance the mental well-being of survivors. Keywords: Cognitive Behavioral Therapy, anxiety, disaster.